Investigation of a Model‐Based Deep Reinforcement Learning Controller Applied to an Air Separation Unit in a Production Environment. Issue 12 (4th November 2021) - Blum, Nicolas; Krespach, Valentin; Zapp, Gerhard; Oehse, Christian; Rehfeldt, Sebastian; Klein, Harald
Abstract: The need for load flexibility and increased efficiency of energy‐intensive processes has become more and more important in recent years. Control of the process variables plays a decisive role in maximizing the efficiency of a plant. The widely used control models of linear model predictive controllers (LMPC) are only partly suitable for nonlinear processes. One possibility for improvement is machine learning. In this work, one approach for a purely data‐driven controller based on reinforcement learning is explored at an air separation plant (ASU) in productive use. The approach combines the model predictive controller with a data‐generated nonlinear control model. The resulting controller and its control performance are examined in more detail on an ASU in real operation and compared with the previous LMPC solution. During the tests, stable behavior of the new control concept could be observed for several weeks in productive operation. Abstract : With the increasing challenges for the process industry in terms of load variation and energy efficiency, new technologies are imperative. Therefore, the latest advances in machine learning are used to investigate an adaptive machine learning based control approach for industrial application using an air separation plant as an example.